So-called delusions in daily life can be broken down and described more accurately with the help of a 7x4-field. - Heiska, Juhani (IJRDO - Journal of Social Science and Humanities Research, 2019)
It was not until the end of the 20th century that a phenomenon known as delusiveness in the daily actions of people attracted significant scientific interest. It is difficult to classify as a mental illness. Nevertheless, it is a collection of skews, and a burden, hindrance, peeve, etc. A tool called 7x4-field has been developed in order to break down the causes of disturbance in mental wellbeing (e.g. divorce), mental disturbance (e.g. obsession), and deviant behavior (e.g. cheating). It contains seven factors: lonelinesses, models, stresses, punishment experiences, losses, avoidances, and life changes, which affect the cornerstones of a good life: social relations, physical exercise, rational functions and irrational functions. This study examined 136 studies, the results of which were placed into the 7x4-field, which in turn confirmed the thesis that the 7x4-field is an effective tool in preemptive mental health work.